2014
DOI: 10.1103/physrevb.89.161407
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption height alignment at heteromolecular hybrid interfaces

Abstract: The formation of metalorganic hybrid interfaces is determined by the fine balance between molecule-substrate and molecule-molecule interactions at the interface. Here, we report on a systematic investigation of interfaces between a metal surface and organic monolayer films that consist of two different molecular species, one donor and one acceptor of electronic charge. Our x-ray standing wave data show that in heteromolecular structures, the molecules tend to align themselves to an adsorption height between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 58 publications
(78 reference statements)
3
27
0
Order By: Relevance
“…Several groups have started to investigate such systems, and, for obvious reasons, prototypical molecules, the homomolecular adsorption of which is well understood, were combined to heteromolecular adsorbate systems in first instance [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Our group has concentrated on the molecules named above, PTCDA, NTCDA and MePcs, and investigated both laterally mixed structures (i.e., two molecules in different stoichiometries combined in one layer) [40][41][42] and heteromolecular stacks of layers whereby each individual layer contains only one species [43][44][45][46].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several groups have started to investigate such systems, and, for obvious reasons, prototypical molecules, the homomolecular adsorption of which is well understood, were combined to heteromolecular adsorbate systems in first instance [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Our group has concentrated on the molecules named above, PTCDA, NTCDA and MePcs, and investigated both laterally mixed structures (i.e., two molecules in different stoichiometries combined in one layer) [40][41][42] and heteromolecular stacks of layers whereby each individual layer contains only one species [43][44][45][46].…”
Section: Introductionmentioning
confidence: 98%
“…In this review paper we present an overview over the activities of our group regarding laterally mixed structures [40][41][42]. We combine investigations of geometric and electronic structure and focus on the interplay of the bonding heights of the molecules and the energy level alignment at the heteromolecular interface.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the assignment of the individual peaks to the CuPc and PTCDA molecules is correct (see discussion below). Very similar models have been successfully used earlier for studying other blends consisting of Phthalocyanine and PTCDA or similar molecules [23,29]. All optimized parameters of the fitting models are summarized in Table I.…”
Section: Core-level Spectramentioning
confidence: 99%
“…In many investigations it was found that the geometric structure and the electronic level alignment at these metal-organic interfaces are determined by the interactions between the molecules themselves, as well as between the molecules and the metal surface. In particular, the charge transfer from the metal substrate into the lowest unoccupied molecular orbital (LUMO), which is the signature of the chemical interaction between the molecule and the surface, is always reflected by the adsorption height of the molecule on the surface [5,6,[21][22][23]. The latter can therefore be seen as a geometric fingerprint of the bonding strength.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, experimental studies on the molecule-substrate bonding distances, which provide the points of reference for adequate theoretical modeling, are rare-in contrast to the numerous experimental studies on single molecule adsorption [15,16] and 2D molecular layers based on intermolecular interactions different than metal coordination [17][18][19][20][21][22][23][24][25][26]. However, these data are crucial for understanding molecule-substrate interactions and of interest for determining possible distortions from the planar geometry of surface-confined 2D MOFs.…”
Section: Introductionmentioning
confidence: 99%